2020
DOI: 10.1167/tvst.9.2.56
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence for Automated Overlay of Fundus Camera and Scanning Laser Ophthalmoscope Images

Abstract: Purpose The purpose of this study was to evaluate the ability to align two types of retinal images taken on different platforms; color fundus (CF) photographs and infrared scanning laser ophthalmoscope (IR SLO) images using mathematical warping and artificial intelligence (AI). Methods We collected 109 matched pairs of CF and IR SLO images. An AI algorithm utilizing two separate networks was developed. A style transfer network (STN) was used to segment vessel structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…There is a relative lack of papers describing retinal image overlay using AI. The efficacy of AI to overlay retinal images taken by different imaging systems has previously been investigated by Cavichini et al 10 In that study from our group, Cavichini et al overlayed matched pairs of colour fundus (CF) photographs and infrared scanning laser ophthalmoscope (IR SLO) images using conventional alignment methods and AI. The AI overlay strategy used consisted of a joint vessel segmentation and a deformable registration model based on the convolutional neural network (CNN).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a relative lack of papers describing retinal image overlay using AI. The efficacy of AI to overlay retinal images taken by different imaging systems has previously been investigated by Cavichini et al 10 In that study from our group, Cavichini et al overlayed matched pairs of colour fundus (CF) photographs and infrared scanning laser ophthalmoscope (IR SLO) images using conventional alignment methods and AI. The AI overlay strategy used consisted of a joint vessel segmentation and a deformable registration model based on the convolutional neural network (CNN).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in AI now allow for the combination of multimodal imaging to be used as a co‐localised database. AI has been previously used in a similar way to categorise or detect disease 8–10 . On the other hand, preliminary trials to overlay multimodal imaging, taken on different platforms, using Microsoft PowerPoint, was not successful (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a lot of research on artificial intelligence (AI) using fundus photographs, OCT, and OCT angiography images [ 36 , 37 , 38 , 39 , 40 ], and there is a highly likelihood that color SLO, which has high image quality with a large amount of information, will be useful for this kind of automatic diagnosis by AI. Indeed, preliminary studies using AI and color SLO have been reported [ 16 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, some state-of-the-art methods should be compared with the local dataset FI-LORE, but due to the lack of reliable source codes and our inability to completely repeat the methods, we failed to put them into further comparison. Finally, there are some artificial intelligence algorithms that have been developed for retinal image registration tasks [22,47,48]. We have compared one deep learning algorithm, but further studies are needed to investigate deep learning in the context of retinal image alignment.…”
Section: Figurementioning
confidence: 99%